Analysis of the Determinants of Healthcare Expenditure Based on Panel Data from 2000–2020 - Malinowski, Piotr (Ekonomia i Prawo. Economics and Law, 2025)
Motivation: The rising costs of healthcare, fueled by aging populations, increasing life expectancy, and expanding access to medical technologies, have intensified the need to understand the underlying drivers of healthcare expenditure. While previous studies often emphasize the income elasticity of healthcare spending, many fail to incorporate broader institutional and socio-demographic factors or rely on limited cross-sectional data from a small subset of countries. Aim: This study aims to provide a comprehensive and updated analysis of the determinants of healthcare expenditures using panel data from 155 countries over the period 2000–2020. By including a wide range of economic, demographic, and institutional variables, and employing a robust two-way fixed effects model, the research seeks to uncover key factors shaping global health spending. Results: The final significant variables influencing healthcare expenditure include GDP per capita, the share of public healthcare expenditure in GDP, the proportion of the population aged 65 and older, urbanization rates, the number of physicians per 1,000 inhabitants and out-of-pocket healthcare expenses. Additionally, a quadratic term for the logarithm of GDP per capita was introduced to account for the non-linear relationship between income and healthcare spending. The findings suggest that both economic and demographic factors are crucial in determining healthcare expenditures, offering insights for policymakers aiming to improve the efficiency of healthcare systems